2020
DOI: 10.1051/0004-6361/202037963
|View full text |Cite
|
Sign up to set email alerts
|

Bars formed in galaxy merging and their classification with deep learning

Abstract: Context. Stellar bars are a common morphological feature of spiral galaxies. While it is known that they can form in isolation, or be induced tidally, few studies have explored the production of stellar bars in galaxy merging. We look to investigate bar formation in galaxy merging using methods from deep learning to analyse our N-body simulations. Aims. The primary aim is to determine the constraints on the mass ratio and orientations of merging galaxies that are most conducive to bar formation. We further aim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 85 publications
2
16
0
Order By: Relevance
“…Patton et al (2020) confirm this effect in cosmological simulations, and demonstrate that close encounters affect galaxy pairs out to separations of ∼280 kpc in 3D space. Each interaction and flyby (Moreno 2012;Sinha & Holley-Bockelmann 2012;L'Huillier, Park & Kim 2015;) is capable of inciting bar formation (Łokas et al 2016;Pettitt & Wadsley 2018;Łokas 2019;Cavanagh & Bekki 2020) and promoting bulge mass growth (Just et al 2010;Bekki & Couch 2011). But more importantly, the cumulative effect of multiple -frequently occurring and long-lived -galaxy encounters may ultimately stimulate the transformation of spirals into lenticulars in dense environments (Moore et al 1996;Boselli & Gavazzi 2006;Cappellari 2013;Joshi et al 2020).…”
mentioning
confidence: 99%
“…Patton et al (2020) confirm this effect in cosmological simulations, and demonstrate that close encounters affect galaxy pairs out to separations of ∼280 kpc in 3D space. Each interaction and flyby (Moreno 2012;Sinha & Holley-Bockelmann 2012;L'Huillier, Park & Kim 2015;) is capable of inciting bar formation (Łokas et al 2016;Pettitt & Wadsley 2018;Łokas 2019;Cavanagh & Bekki 2020) and promoting bulge mass growth (Just et al 2010;Bekki & Couch 2011). But more importantly, the cumulative effect of multiple -frequently occurring and long-lived -galaxy encounters may ultimately stimulate the transformation of spirals into lenticulars in dense environments (Moore et al 1996;Boselli & Gavazzi 2006;Cappellari 2013;Joshi et al 2020).…”
mentioning
confidence: 99%
“…While there is overwhelming evidence that the centre of the Milky Way hosts a bar (e.g., Queiroz et al 2020;Anders et al 2019), its origins are still poorly understood. Studies using N-body simulations (e.g., Cavanagh & Bekki 2020;Peirani et al 2009) have indicated that bar formation in disc galaxies can be triggered by minor mergers, with mass ratios of 0.1 being most conducive (Cavanagh & Bekki 2020). Furthermore, observations of the Milky Way's bulge (Surot et al 2019) have found that its stars are largely over 7.5 Gyr old, roughly corresponding to the time of the GS merger.…”
Section: Bar Formationmentioning
confidence: 99%
“…Each architecture is built using Keras (Chollet et al 2015), a high-level machine learning interface. The first CNN, referred to as C1, is based on our previous work (Cavanagh & Bekki 2020), and was originally designed for the binary classification of 50 × 50 imagery. This architecture consists of a single block of convolution and pooling layers (2 Conv2D plus a MaxPooling), a penultimate Dense layer with 256 nodes, and the output Dense layer which contains either 3 or 4 nodes for 3-way or 4-way classification.…”
Section: Model Architecturesmentioning
confidence: 99%